Stiffness enhancement of magnetorheological foam by structural modification using silica nanoparticles additive - Khaidir, Rahayu Emilia Mohamed; Nordin, Nur Azmah; Mazlan, Saiful Amri; Abd Rahman, Hamimah; Ubaidillah,; Abdul Aziz, Siti Aishah; Nazmi, Nurhazimah (Frontiers in Materials, 2022)
Magnetorheological (MR) foam is a new porous smart material that change its properties continuously, actively, and reversibly in response to controllable external magnetic stimuli. Unfortunately, the stiffness or also known as the storage modulus of MR foam is still rather low and insufficient in the range of below 100 kPa only due to weak interparticle interaction between CIPs and foam matrix, which consequently restricted the potential of MR foam to be used in future sensor applications. Therefore, the aim of this research is to enhance the structural and storage modulus of MR foam by adding silica nanoparticles as an additive. Consequently, MR foam samples with different compositions of silica nanoparticles in the range of 0 to 5 wt.% were prepared via the in-situ method. The rheological properties were tested under oscillatory shear mode with the absence and presence of magnetic fields using a rheometer, with the input parameters of strains between 0.001 to 10% and a range of magnetic flux density between 0 to 0.73 T for the magnetic field sweep test. The rheological findings show that the addition of silica nanoparticles, particularly at 4 wt.% have enhanced the storage modulus of MR foam by 260%, which attributed to the highest stiffness from 45 to 162 kPa. Meanwhile, the change of storage modulus under the influence of magnetic fields (0 T to 0.73 T) somehow showed a small increment, about ∆1 kPa for each concentration of silica nanoparticles in the MR foams, due to the non-magnetic behavior of the silica. The morphological characteristics of MR foams were done by using a variable pressure scanning electron microscope (VPSEM) that was equipped with x-ray spectroscopy for the elemental analysis of MR foam. The micrographs demonstrated large-open cell pores for MR foam while MR foam with silica nanoparticles exhibited more closed-cell pores, associated with the enhancement of its storage modulus. It indicates that the silica nanoparticles have encouraged well dispersion of the particles in the foam matrix thus improving and strengthening the microstructure of MR foams through the formation of silane coupling bonds of silica in the filler-matrix structure.